Prevalence and social determinants of smoking among men in Mauritius: a cross-sectional study - Miguel San Sebastián; Tuomilehto Jaakko; Stefan Söderberg; Paul Zimmet; Bhushan Ori; Jaysing Heecharan; Osvaldo Fonseca-Rodríguez; Sudhirsen Kowlessur (Taylor & Francis Group, 2024)
Background Mauritius has implemented a range of stringent policies to control smoking and promote public health. Regular monitoring focuses on the prevalence of tobacco use, yet there is a gap in understanding its socio-economic patterns. Objective The aim of this study was to estimate the prevalence of tobacco smoking and to identify the social determinants associated with smoking among men in Mauritius in 2021. Methods This is a cross-sectional population-based study conducted by the Ministry of Health and Wellness during 2021. In total, 3622 individuals participated (response rate of 84.1%), of which 1663 were men (45.9%). The study mainly focused on men given the low prevalence of smoking among women. Daily smoking was the outcome and a series of sociodemographic and socioeconomic factors were included as independent variables. Prevalence ratios (PR) and their 95% confidence intervals (95% CI) were estimated to fulfill the study objective. Results The prevalence of smoking among men was 30.4%. People in the 25-34 age group (PR = 1.65; 95% CI: 1.12-2.41), those separated, divorced or widowed (PR = 1.57; 95% CI: 1.16-2.11), the ethnic groups Muslim-Mauritians (PR = 1.70; 95% CI: 1.00-2.89) and Creoles (PR = 1.97; 95% CI: 1.16-3.35), and those with secondary (PR = 1.29; 95% CI: 1.00-1.67) and primary education (PR = 1.47; 95% CI: 1.10-1.98) were statistically significantly associated with daily smoking. Conclusions Although a gradual decline in smoking prevalence was observed compared with the previous 2015 survey, the Ministry of Health and Wellness should persist in fortifying its anti-smoking measures and concentrate on crafting tailored interventions aimed at the vulnerable groups identified in this study.